Penggunaan Aplikasi Photomath pada Pembelajaran Matematika: Systematic Literature Review - Rifa’i, Muhammad; Yahfizham (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
The purpose of this research is to determine the benefits of using the photomath application in learning. Nowadays, students can use media to help solve problems when working on math problems, including watching learning videos on YouTube, or even using math applications such as Photomath. This research uses the Systematic Literature Review method from journals published in 2022 & 2023. The results of this research are that the use of the photomath application can help the mathematics learning process in class. The photomath application is equipped with solution steps so that students can understand how to solve the given math problems.